Coumarins of Haplopappus Multifolius and Derivative as Inhibitors of Lox: Evaluation In-Vitro and Docking Studies - Torres-Gaona, M; Modak-Canobra, B; Mascayano-Collado, C (Sociedad Chilena de Quimica, 2013)
Several natural compounds containing a coumarin moiety have been reported. They have multiple biological activities, e. g. , as scavengers of reactive oxygen species (ROS) and to reduce the inflammatory processes by inhibition of enzymes like COX or LOX. A study was made of the inhibitory capacity of seven natural coumarins and one derivative of esculetin, against soybean 15-lipoxygenase (15-sLOX). The studied coumarins showed interesting degrees of inhibition compared to quercetin, a known LOX inhibitor. Docking studies of some compounds into the binding site of 15-sLOX and 5-hLOX were also made.